The Therapeutic Efficacy of Dendrimer and Micelle Formulations for Breast Cancer Treatment - Sibusiso Alven; Blessing Atim Aderibigbe (MDPI AG, 2020)
Breast cancer is among the most common types of cancer in women and it is the cause of a high rate of mortality globally. The use of anticancer drugs is the standard treatment approach used for this type of cancer. However, most of these drugs are limited by multi-drug resistance, drug toxicity, poor drug bioavailability, low water solubility, poor pharmacokinetics, etc. To overcome multi-drug resistance, combinations of two or more anticancer drugs are used. However, the combination of two or more anticancer drugs produce toxic side effects. Micelles and dendrimers are promising drug delivery systems that can overcome the limitations associated with the currently used anticancer drugs. They have the capability to overcome drug resistance, reduce drug toxicity, improve the drug solubility and bioavailability. Different classes of anticancer drugs have been loaded into micelles and dendrimers, resulting in targeted drug delivery, sustained drug release mechanism, increased cellular uptake, reduced toxic side effects of the loaded drugs with enhanced anticancer activity in vitro and in vivo. This review article reports the biological outcomes of dendrimers and micelles loaded with different known anticancer agents on breast cancer in vitro and in vivo.